Simulating maize phenology as a function of air temperature - Streck, Nereu Augusto; Lago, Isabel; Gabriel, Luana Fernandes; Samboranha, Flavia Kaufmann (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this study was to adapt a nonlinear model (Wang and Engel – WE) for simulating the phenology of maize ( Zea mays L.), and to evaluate this model and a linear one (thermal time), in order to predict developmental stages of a field-grown maize variety. A field experiment, during 2005/2006 and 2006/2007 was conducted in Santa Maria, RS, Brazil, in two growing seasons, with seven sowing dates each. Dates of emergence, silking, and physiological maturity of the maize variety BRS Missões were recorded in six replications in each sowing date. Data collected in 2005/2006 growing season were used to estimate the coefficients of the two models, and data collected in the 2006/2007 growing season were used as independent data set for model evaluations. The nonlinear WE model accurately predicted the date of silking and physiological maturity, and had a lower root mean square error (RMSE) than the linear (thermal time) model. The overall RMSE for silking andphysiological maturity was 2.7 and 4.8 days with WE model, and 5.6 and 8.3 days with thermal time model,respectively.